2014
DOI: 10.4103/0973-1482.131451
|View full text |Cite
|
Sign up to set email alerts
|

Adipose derived stem cells isolated from omentum: A novel source of chemokines for ovarian cancer growth

Abstract: Omental adipose tissue may play crucial roles for tumor promotion through the expression of tumor promoting chemokines. Accordingly, tumor surrounding adipose tissue may be a novel target for immunotherapy of cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The pro-growth effects of BMSCs on cancer have been widely demonstrated [ 31 - 33 ]. Recent reports led to similar conclusions that ADSCs promoted cancer growth and metastasis [ 8 - 11 ]. Moreover, Eterno et al found that ADSCs could enhance breast tumor self-renewal and facilitate breast cancer recurrence via HGF/c-Met axis [ 21 ].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The pro-growth effects of BMSCs on cancer have been widely demonstrated [ 31 - 33 ]. Recent reports led to similar conclusions that ADSCs promoted cancer growth and metastasis [ 8 - 11 ]. Moreover, Eterno et al found that ADSCs could enhance breast tumor self-renewal and facilitate breast cancer recurrence via HGF/c-Met axis [ 21 ].…”
Section: Discussionmentioning
confidence: 71%
“…Although current knowledge of the biological impacts of MSCs on tumor development is greatly improved, the underlying effects of MSCs from different origins remain controversial. Accumulating evidence indicates that ADSCs promote the tumor growth and metastasis of various cancers [ 8 - 11 ], whereas conflicting reports reveal the anti-tumorigenic potentials of ADSCs such as anti-proliferation and pro-apoptosis [ 12 - 14 ]. Hence, the elusive role of ADSCs in tumor development causes the safety concerns in clinical utilization.…”
Section: Introductionmentioning
confidence: 99%
“…The role of IP-10 (CXCL-10) has not been well studied in relation to progression of gliomas. However, a recent study by Rezaeifard et al [ 74 ] has implicated adipose stem cell derived IP-10 in the pathogenesis of ovarian cancer. Further studies in this direction may provide valuable insight into alternative or additional mechanisms by which IL-17–IL-17R interaction could promote GSC stimulation and glioma progression.…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, ADSCs have gained increasing attention for their role in supporting tumor growth and progression [51]. Many authors have demonstrated that ADSCs, and particularly those from omental adipose tissue, can increase ovarian cancer cell proliferation and promote a shift toward a more aggressive, invasive, and metastatic phenotype [10,31,52,53] (Figure 2). taxane-induced cell death.…”
Section: Adscs In the Ovarian Cancer Microenvironmentmentioning
confidence: 99%
“…ADSCs are attracted to the tumor site and have a specific tumor homing due to several chemotactic factors in the tumor microenvironment. In particular, in the omentum of ovarian cancer patients, high levels of CXCL-10 and CCR5 have been described [53]. Furthermore, recruited ADSCs secreted IL-10, which has a strong chemotactic activity for Treg lymphocytes and could play a role in immunosuppression in the tumor microenvironment.…”
Section: The Effects Of Tumor Cells On Adsc Recruitment and Adsc Phenotypic Changesmentioning
confidence: 99%